2009
DOI: 10.1007/s00464-009-0763-1
|View full text |Cite
|
Sign up to set email alerts
|

Mesh-fixation method and pain and quality of life after laparoscopic ventral or incisional hernia repair: a randomized trial of three fixation techniques

Abstract: BackgroundPersistent, activity-limiting pain after laparoscopic ventral or incisional hernia repair (LVIHR) appears to be related to fixation of the implanted mesh. A randomized study comparing commonly used fixation techniques with respect to postoperative pain and quality of life has not previously been reported.MethodsA total of 199 patients undergoing non-urgent LVIHR in our unit between August 2005 and July 2008 were randomly assigned to one of three mesh-fixation groups: absorbable sutures (AS) with tack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
96
3
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(105 citation statements)
references
References 20 publications
3
96
3
3
Order By: Relevance
“…At the 3-month follow-up, no differences were found between the VAS pain scores (30). In a second RCT (n = 68), helical tack fixation in 2 concentric rows (titanium, double-crown technique) caused significantly more pain over a period of up to 3 months postoperatively compared to permanent transfascial sutures (polypropylene) (31).…”
Section: Outcomes Of the Surgical Techniquesmentioning
confidence: 89%
“…At the 3-month follow-up, no differences were found between the VAS pain scores (30). In a second RCT (n = 68), helical tack fixation in 2 concentric rows (titanium, double-crown technique) caused significantly more pain over a period of up to 3 months postoperatively compared to permanent transfascial sutures (polypropylene) (31).…”
Section: Outcomes Of the Surgical Techniquesmentioning
confidence: 89%
“…[18][19][20][21][22] Our study showed no significant relation between mesh fixation with transfascial sutures and non-absorbable tackers and recurrence of hernia, which is consistent with the existing literature. 23,24 There has been a recent focus on the use of fibrin glue for mesh fixation, particularly in areas such as the subcostal margins and close to the xiphisternum and pelvis. Other studies have emphasised that mesh fixation using fibrin glue in patients with LIVHR is associated with less postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…9 This method allows the surgeon to avoid using tacks or transabdominal sutures for suture fixation, which are often cited as the culprit for laparoscopic postoperative pain. 10 The ergonomic features of the robot also give the surgeon the opportunity to create a peritoneal flap for preperitoneal mesh placement to prevent meshrelated intra-abdominal complications and reduce the risk of migration and lateral detachment, which are often cited as the cause of recurrence. 11,12 To date, there are no case reports on the use of the robotic platform to repair a nonmidline ventral hernia from a hand-assist site.…”
Section: Discussionmentioning
confidence: 99%